Implementation of Productive Waqf as a Shariah-Based Economic Empowerment Solution in the Community in the Neighborhood of Rizki Bakti Negeri Foundation in Pekanbaru - Wali Saputra (Indo Publishing, 2025)
This community service initiative seeks to actualize the principle of productive waqf as a sharia-compliant economic empowerment strategy within the community surrounding the Yayasan Rizki Bakti Negeri Pekanbaru. The primary issues discerned include the populace's inadequate comprehension of productive waqf, in addition to the insufficient deployment of waqf assets in enduring economic endeavors. The methodology for implementation is delineated into four phases: preparatory measures, execution, assessment and documentation, as well as the perpetuation of the evaluative outcomes. These initiatives encompass training sessions, mentorship, the collection of cash waqf, and the formation of business units managed collectively using waqf resources. The outcomes of the initiatives indicate an enhancement in the community's awareness of productive waqf, the establishment of local waqf management collectives, and the realization of business entities in the form of sharia-compliant food kiosks capable of generating profits and uplifting the surrounding populace. Beyond the economic ramifications, these initiatives also fortify the spiritual values and social cohesion within the community. The evaluation process was conducted through empirical field observations, surveys, and open dialogue forums, revealing that a significant majority of participants endorsed the sustainability of the program and expressed a desire for its expansion into additional sectors. The program has effectively laid the groundwork for an initial community-oriented productive waqf ecosystem characterized by transparency, participation, and adherence to Sharia principles. It is anticipated that this initiative can be replicated in other locales as a paradigm of inclusive and sustainable Islamic economic empowerment.